The Influence of Community Participation and Institutional Transparency on the Accountability of Village Financial Reports in Tebaban Village, Suralaga District - Ma'wa, Jannatul; Ihsan, Sahrul (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to examine the extent to which community participation and institutional transparency influence the level of accountability in village financial reporting. The background of this research stems from the urgency of accountability as a key element in the management of village funds, along with indications that community participation remains limited to formal aspects, and that transparency practices have not yet been fully implemented optimally at the village level. The research was conducted in Tebaban Village, Suralaga District, East Lombok Regency, using a quantitative approach. Data were collected through questionnaires distributed to 57 respondents consisting of village officials and community representatives. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, with the assistance of SmartPLS software. The findings reveal that the community participation variable does not have a significant influence on the accountability of village financial reports. This suggests that community involvement in financial management at the village level remains procedural rather than substantive. On the other hand, institutional transparency shows a significant and positive effect on accountability, reinforcing the assumption that open access to information can enhance accountability in the management of public finances. These findings contribute theoretically to the development of literature in the field of village financial governance, while also offering practical recommendations for village governments to strengthen transparency practices and encourage more meaningful and active community participation.